Two species of Prodistomum Linton, 1910 (Digenea: Lepocreadiidae) from marine fishes of Australia - Bray, R. A.; Cribb, T. H. (Systematic Parasitology, 1996)
Prodistomum angelae (Kruse, 1981) n. comb. [originally Lepocreadium] is redescribed from the type-host, Scorpis georgiana, from off southwestern Western Australia. P. keyam n. sp. is described from Monodactylus argenteus from off southeastern Queensland. It differs from other members of the genus in its short ejaculatory duct. The genus Prodistomum Linton is discussed and redefined, and an updated key and record list of the nine recognised species are given.